PENGARUH LITERASI KEUANGAN, PEMBELAJARAN AKUNTANSI KEUANGAN DAN TEMAN SEBAYA TERHADAP PENGELOLAAN KEUANGAN MAHASISWA DI ERA PANDEMI COVID-19 - Sukma Ragil Pamungkas; Han Tantri Hardini (Inspiratif Pendidikan, 2022)
Current student financial management is dependent on financial literacy, financial accounting learning and peers. Related to student financial managemet, it can be caused by three factors such as : financial literacy, financial accounting learning and peers. This study aims to determine the effect of financial literacy, financial accounting learning and peers on student financial management in the era of the covid-19 pandemic. In this research uses quantitative research. Data collection using a questionnaire with a population of 180 students. The sample technique used is a simple random sampling, provided that you have taken financial accounting courses. The data analysis technique used is multiple regression analysis. The results of the first study showed that financial literacy had no significant effect on student financial management. Second, learning financial accounting has a significant effect on student financial management. Third, peers have a significant effect on student financial management. And lastly, financial literacy, financial accounting learning and peers simultaneously affect student financial management in the era of the covid-19 pandemic.